The Aesthetic Features Of Metaphorical Imagery In The Poem Umm Jundub From The Diwan Of Imru' Al-Qais: A Descriptive And Analytical Study/ جماليات الصور الاستعارة في قصيدة أم جندب لديوان امرئ القيس دراسة وصفية وتحليلية - Jaafar, Nuraznan Bin; Bin Yahaya, Mohd Firdaus; Binti Mohamad Suhane, Shuhaida Hanim (Ijaz Arabi Journal of Arabic Learning, 2025)
This study investigates the aesthetic value of metaphorical imagery in the poem Umm Jundub from the Diwan of Imru’ al-Qais. It adopts a literary-rhetorical approach that combines both descriptive and analytical methods. The research identifies and interprets key metaphorical expressions to reveal their rhetorical significance in pre-Islamic Arabic poetry. The study is framed within a broader awareness of rhetorical expression (al-bayan), aiming to extract, describe, and analyze the artistic imagery that characterizes the selected verses. Emphasis is placed on uncovering deeper meanings and rhetorical functions embedded in the poet’s metaphors. This analysis draws upon three primary editions of the Diwan, compiled by al-Zuzani, Yasin al-Ayyubi, and Abu al-Fadl Ibrahim. The findings of this research are expected to contribute to the field of Arabic rhetoric and classical literature by offering theoretical insights and practical applications for interpreting figurative language in early Arabic poetry.